The Effect of Leadership, Organizational Culture, Emotional Intellegence, and Job Satisfaction on Performance - Muhammad Ilyas; Tamrin Abdullah (Institute of Advanced Engineering and Science, 2016)
This Researchaims to study the influence of Leadership, Organizational Culture, Emotional Quotation, and Job Satisfaction to Teacher Performance of Senior High School at Palopo Municipality South Sulawesi. Samplestudy involving 78 Teachers.The results are: (1) Leadership directly effects teacher performance (2)Emotional quotation directly influence teacher performance, (3) Job Satisfaction directly effects teacher performance, (4) Leadership directly effects job satisfaction, (5) Organizational Culture directly effects job satisfaction, (6) Emotional Quotattion directly effects job satisfaction.Based on this research, the factors of Leadership, Organizational Culture, Emotional Quotation, and Job Satisfaction to Teacher Performance should be developed by Central and Local Governmenteither Palopo or South Sulawesi.